THE WASTEWATER TREATMENT OF ENTERPRISES OF THE CONSTRUCTION INDUSTRY BY MODIFIED NATURAL MINERAL - Elena Viktorovna Moskvicheva; Pavel Alexeyevich Sidyakin; Irina Sergeevna Alyohina; NataljaValerievna Vahilevich (Современная наука и инновации)
The article presents the results of studies of the properties developed on the basis of the flask sorption filter material. The use of this material in practice will contribute to the organization of high-quality water recycling in industrial plants.